UNCOVERING THE MEANINGS OF FIGURATIVE LANGUAGE USED IN SELECTED TAYLOR SWIFT SONGS - Ngadu, Dominikus; Pratiwi, Desak Putu Eka; Candra, Komang Dian Puspita (LITERA : Jurnal Bahasa Dan Sastra, 2022)
ABSTRACTSongs can often cheer someone us up when listening to it. However, a song does not forget thefigurative language used by the songwriters to make it sound appealing to the listeners. Thepurpose of this study is to find and analyze the meanings of the figurative language used inselected Taylor Swift song lyrics. The data in this study were taken from Taylor Swift's songs.The study utilized the qualitative method by presenting an overview of the data. Data collectionwas carried out using the observation method with the following steps: downloading songlyrics, then selecting data using figurative language. In data analysis, two theories were usedby researchers to analyze figurative language and its meanings, and these theories are theFigurative Language theory from Knickerbocker and Reninger (1963) and the Meaning theoryused is the theory proposed by Leech (1974). From the results of the study obtained 29 datawhich include: metaphor (7 items or 23,33%), personification (5 items or 16,16%), simile (5items or 16,66%), hyperbole (5 items or 16,66%), metonymy (2 items or 6,66%), paradox (2item or 6,66%), synecdoche (1 item or 3,33%), irony (1 item or 3,33%), and allusion (1 item or6,66%). The dominant figurative language used is metaphor for comparing two different thingsso that they can become a unified whole.Keywords: song lyrics, meaning, figurative languageABSTRAKLagu adalah salah satu hal yang dapat membuat kita semangat saat mendengarkannya.Namun, sebuah lagu tidak melupakan bahasa kiasan yang digunakan oleh penulisnya untukmembuatnya terdengar menarik bagi pendengarnya. Tujuan dari penelitian ini adalah untukmengetahui dan menemukan makna dari bahasa kiasan yang digunakan dalam lirik laguTaylor switt. Data dalam penelitian ini diambil dari lagu Taylor Swift. Penelitian dilakukandengan menggunakan metode kualitatif dengan penyajian gambaran data. Pengumpulan datadilakukan dengan metode observasi dengan langkah-langkah sebagai berikut: mengunduh liriklagu, kemudian memilih data menggunakan bahasa kiasan. Dalam analisis data, ada dua teoriyang digunakan peneliti dalam penelitian ini untuk menemukan bahasa kiasan dan maknanya,dan teori tersebut adalah teori Bahasa Kiasan dari Knickerbocker dan Reninger (1963:367)dan teori Arti yang digunakan adalah teori dari Knickerbocker dan Reninger (1963:367).Lintah (1974). Dari hasil penelitian diperoleh 29 data yang meliputi: metafora (7 item atau20%), personifikasi (5 item atau 16,66%), simile (5 item atau 16,66%), hiperbola (5 item atau16,66%), metonimi (2 item atau 6,66%), paradoks (2 item atau 6,66%), synecdoche (1 itematau 3,33%), ironi (1 item atau 3,33%), dan kiasan (1 item atau 3,33%. Bahasa kiasan yangdominan adalah metafora karena penulis membandingkan dua hal yang berbeda sehinggamenjadi satu kesatuan yang utuh.Kata kunci: lirik lagu, makna, bahasa kiasan